Inhibition of Calcium Oxalate Crystallization by Graft Copolymers - Kirboga, Semra; Oner, Mualla (AMER CHEMICAL SOC, 2009)
Influence of graft copolymers with different architecture on spontaneous batch crystallization of calcium oxalate was investigated. The series of water-soluble polyethyleneglycol methacrylate-vinylsulfonic acid graft copolymers [(PEG-MA)-co-VS] and homopolymer of vinylsulfonic acid have been made, by radical polymerization, with defined molecular weight and structure. The presence of polymers inhibited the crystal growth of calcium oxalate possibly through adsorption onto the active growth sites for crystal growth due to the charge and hydrophilic effects. The higher inhibition efficiency of vinylsulfonic acid homopolymer is related to the maximum surface charge density due to adsorbed polymer. The homopolymer influenced both the morphology and phase transformation of calcium oxalate crystals. Polyelectrolyte effect,, were interpreted in terms of the adsorption of inhibitors onto the active growth sites on the crystal surface.
Keywords: MONOHYDRATE CRYSTAL-GROWTH; MAGNESIUM-IONS; POLYELECTROLYTES; CITRATE; URINE; ACID; ARCHITECTURE; OSTEOPONTIN; ADSORPTION; NUCLEATION; Chemistry; Crystallography; Materials Science